Development of Learning Modules Assisted by Augmented Reality (AR) to Improve Learning Outcomes of High School Students on the Concept of the Circulatory System - Qiswatun Mukhoyyaroh; Latif Sofiana Nugraheni; Ripauji Ripauji; Siti Hanna Sumedi (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2023)
The learning outcomes of high school students on the circulatory system concept have not reached the expected target. The achievement of basic competencies or learning objectives are not achieved because the learning resources that have been used by teachers and students are not able to strengthen The achievement of basic competencies or learning objectives is not achieved because the learning resources that have been used by teachers and students are not able to strengthen concept abstraction for the topic of the circulatory system.. Augmented Reality (AR) technology is a technology that infuses information from the virtual world and displays it in real (3D) with the help of a computer or mobile phone. This study aims to produce Augmented Reality (AR) assisted learning modules to improve learning outcomes in circulatory system concept. The type of research used is Research and Development (R&D) research with a research design developed by Hanafin and Peck that consists of three phases, that is the needs analysis phase, design phase, and development - implementation phase. Data collection techniques in this study used interviews and questionnaires. The results of this study indicate that Augmented Reality (AR) assisted learning module on circulatory system topic was declared very good (86.6%) by experts with review from media experts (85.3%), material experts (90.2%) and experts language (84.3%). This module has characteristics of a printed learning module which includes 3D images equipped with Augmented Reality (AR) technology.. However, it is not yet known how effective this module in improving learning outcomes because it has not passed the product effectiveness assessment. Therefore, the researcher suggests further research, to test the effectiveness of this learning module on student learning outcomes.